Selective laser sintering 3D-Printed conductive thermoplastic polyether-block-amide elastomer/carbon nanotube composites for strain sensing system and electro-induced shape memory. (November 2022) - Ding, Bowen; Zhang, Yuancheng; Wang, Jiqiang; Mei, Shuxiang; Chen, Xiaoyin; Li, Siyuan; Zhao, Wei; Zhang, Xiaomeng; Shi, Ge; He, Yanjie; Cui, Zhe; Fu, Peng; et al.
Abstract: A novel mixed powders made up of laboratory-made thermoplastic polyether-block-amide (TPAE) and multiwalled carbon nanotubes (MWCNTs) for the selective laser sintering (SLS) 3D printing have been prepared through an environment-friendly approach and the carbon nanotube conductive network structure is established in the SLS-processed nanocomposite devices. The electrical properties, strain sensing property and electro-induced shape memory effect of flexible TPAE/MWCNTs nanocomposites are fully investigated. The conductivity of TPAE/MWCNTs nanocomposites increases as the MWCNTs content increases owing to the interconnected MWCNTs conductive network. During compressing test with different deformation strain and speed, the SLS-processed flexible sensor exhibits a regular, fast, sensitive and stable cyclic response which shows its great potential for artificial electronic skin, human-machine interface and health monitoring. The TPAE-5.0C nanocomposite also possessed an excellent shape recovery ability during electro-induced shape memory cycle which was triggered by Joule heat under DC voltage. The MWCNTs-TPAE powder prepared here provides a novel material for SLS 3D-printing and the SLS-processed devices with outstanding performance and multiple functions will be very useful for developing flexible and lightweight wearables in the future. Graphical abstract: Image 1 Highlights: A novel MWCNTs-TPAE powder for SLS 3D-printing was prepared. TPAE/MWCNTs nanocomposite possesses excellent electrical properties. A flexible strain sensor made of TPAE/MWCNTs nanocomposite was fabricated. The electro-triggered shape recovery of TPAE/MWCNTs nanocomposite was realized.